Al-Masiri's perspective on secularism : an analytical study - Sila, Boukary (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This research carries out a study on al-Masiri's view on secularism. In fact, al-Masiri has challenged the traditional proposition that 'secularism' is 'the separation of religion from state', and has deemed it 'simplistic or reductionist'; because, according to him, it overlooks the epistemological as well as the social underpinnings of the term. As such, he suggests a proposition, in lieu of the traditional one, that is all-encompassing able to represent all dimensions that are latent in 'secularism' and that have been overlooked consciously and unconsciously by western social scientists. As an antithesis to the traditional proposition, al-Masiri maintains that secularism is a 'worldview'. Hence, the study examines the grounds on which al-Masiri's claim rests and the methodology he followed in concluding such a finding. To understand how the term was traditionally perceived, the study presents a brief historical account of secularism and its development in the West and how it found its way to the Muslim world, with special reference to the Arab world. In addition, the study provides a conceptual framework with regard to the mainstream definitions of secularism. As far as al-Masiri's perceptive on the subject matter is concerned, the study examines his life and thought to know how his thought developed and how this was to affect his view that secularism is a worldview and not only a political process. The study uses a qualitative and library based approach where data is exclusively sought from books and journals. Finally, the study concluded that there are many social phenomena in our Muslim societies that can be described as secularist, nonetheless, we are completely not only unaware of their presence but also involved deeply in it. Therefore, the study suggests that al-Masiri's view needs to be taught in schools and universities in order to educate our children and the generation to come—the leaders of tomorrow, and make them aware of the epistemological underpinnings that secularism entails so that we can avoid, combat, and uproot them from our Muslim societies.